Perbandingan Metode Konstruksi Dinding Bata Merah dengan Dinding Bata Ringan - Tedja, Michael; Charleshan, Charleshan; Efendi, Jefri (Bina Nusantara University, 2014)
The development of technology and the demands on the speed of the construction project cause the material manufacturers compete to create a new material that can accelerate the process to build a building. Wall is one of the non-structural elements on a building. Both low-rise building and high-rise building are no doubts using this material. Wall works can use two different types of material, such as brick wall made of red clay and light brick wall made of cement, silica sand, and limestone. In the construction process wall is needed in a large amount of area, so the difference of the price should be examined in choosing the type of the material to gain efficient cost. The purpose of this study is to determine which method of wall construction is more efficient in terms of cost and time, the use of red brick wall or brick wall light. The study was conducted using survey, comparative, literature study method. Results indicate that both methods have advantages and disadvantages. Red brick wall method is cheaper in the cost of the process, while the lighter brick wall method much faster in the process.